Comparison of Lipid Profile and Insulin Sensitivity in Rabbits Fed with High-Fat or High Fructose Diets - Kachiwal, Allah Bux; Mangi, Raheela; Malhi, Mool Chand; Syed, Mehboob Alam (Indus Journal of Bioscience Research, 2024)
Obesity and metabolic syndrome are significant global health challenges influenced by dietary and lifestyle factors. This study aimed to develop an experimental rabbit model of obesity and metabolic syndrome using high-fat and high-fructose diets over 11 weeks. Rabbits were divided into three groups: group A (control) fed a basal diet, group B fed a high-fat diet, and group C fed a high-fructose diet. Key metrics assessed included body weight, fat mass, basal glycemia, glucose infusion rate (GIR), total cholesterol, triacylglycerol (TAG), and non-esterified fatty acid (NEFA) levels.Group B (high-fat diet) showed the highest body weight (2640±70g) and fat mass (90±12.2g), while group A (control) had the lowest values (2420±40g and 63.3±9.5g, respectively). Group C (high-fructose diet) exhibited the highest basal glycemia (5.52±0.31 mmol/l) and TAG levels (2±0.30 mmol/l). GIR was highest in group A (18.5±1.2 mg/kg/min) and lowest in group B (12.9±2.0 mg/kg/min). Total cholesterol was highest in group A (2.04±0.14 mmol/l) and lowest in group C (1.83±0.14 mmol/l). NEFA levels peaked in group C (0.41±0.04 mmol/l) and were lowest in group A (0.3±0.04 mmol/l).The study demonstrated that high-fat and high-fructose diets induce distinct metabolic changes in rabbits, modeling key features of obesity and metabolic syndrome. These findings highlight the differential impacts of these diets, providing a basis for further research into the mechanisms and dietary influences driving these conditions